A compressed sensing based approach on discrete algebraic reconstruction technique - Demircan Türeyen, Ezgi; Kamaşak, Mustafa Erşel (IEEE, 345 E 47th St, New York, Ny 10017 USA, 2015)
Discrete tomography (DT) techniques are capable of computing better results, even using less number of projections than the continuous tomography techniques. Discrete Algebraic Reconstruction Technique (DART) is an iterative reconstruction method proposed to achieve this goal by exploiting a prior knowledge on the gray levels and assuming that the scanned object is composed from a few different densities. In this paper, DART method is combined with an initial total variation minimization (TvMin) phase to ensure a better initial guess and extended with a segmentation procedure in which the threshold values are estimated from a finite set of candidates to minimize both the projection error and the total variation (TV) simultaneously. The accuracy and the robustness of the algorithm is compared with the original DART by the simulation experiments which are done under (1) limited number of projections, (2) limited view problem and (3) noisy projections conditions.
Keywords: Discrete Tomography; image reconstruction; algebraic reconstruction techniques; global thresholding; compressed sensing; total variation minimization; Art